The Effects of Planting Date and Tillage Practice on Growth and Yield of Maize and Soybean in Rotation with Winter Onion - Jihyeon Lee; Miri Choi; Nayoung Choi; Gamgon Kim; Yunho Lee; Huisu Bae; Chaein Na (Agronomy, 2022)
Introducing summer staple crops to diversify conventional summer paddy rice (Oryza sativa L.) and onion (Allium cepa L.) rotation is important for sustainable agriculture. Herein, we evaluate the effects of planting date (early June to late July) and tillage practice (deep cultivation, DC; conventional tillage, CT) on two maize and soybean cultivars over 4 years (2018–2021) in converted paddy soil in Korea. Due to the growing degree-day differences, the yields of June and July planted crops were 7050 and 5554 total digestible nutrient kg ha−1, respectively, for silage corn, and 7410 and 6473 marketable fresh ear kg ha−1, respectively, for waxy corn. Delaying soybean planting from June to July significantly reduced crops’ yield and interfered with field preparation for the following winter cash crops. The June and July planting yields were 2672 and 2090 kg ha−1, respectively, for large-grain soybean, and 2416 and 1861 kg ha−1, respectively, for small-grain soybean. Deep tillage had no effect on summer crops yield. Additionally, the summer crop growing practice had no residual effect on onion yield. Our study recommends mid to late June planting for growers who wish to introduce maize and soybean in rotation with winter onion in the region.